The Size of the Influence of Compensation on Employee Work Productivity - Yantu, Irwan; Pakaya, Abd Rahman (International Journal of Multidisciplinary Applied and Science Research, 2025)
Providing fair compensation is important for companies to increase employee motivation so that they can increase their work productivity. This study aims to test how much influence compensation has on employee work productivity at PT Nenggapratama Mobilindo Gorontalo. The data in this study were obtained through questionnaires to respondents, the data obtained primarily will be analyzed using regression. The results of this study indicate that compensation has a significant effect on employee work productivity at PT Nenggapratama Mobilindo Gorontalo. The positive regression coefficient indicates that if the compensation variable given is greater, employee work productivity will also be greater. It can also be seen that the ability of the independent variable to explain the dependent variable is good with a determination coefficient value of 22.8%. This is because there are still various other factors that affect employee work productivity